Total synthesis of diverse oxygenated carbazoles by modified aromatization using molecular iodine. Issue 6 (10th February 2016) - Humne, Vivek T.; Naykode, Mahavir S.; Ghom, Monica H.; Lokhande, Pradeep D.
Graphical abstract: Abstract: A convenient route has been developed for mono and dioxygenated carbazole alkaloids from 1-oxotetrahydrocarbazoles. The key step of the synthetic route is the aromatic process of 1-oxotetrahydrocarbazoles using molecular iodine. To our knowledge, this is the first report to manifest a direct synthesis of clausine E, mukonine, mukoeic acid and mukoline, from readily available ester-containing building blocks by using Fischer–Borsche method.